Pelatihan Pemberdayaan Lansia Dengan Cara Bercocok Tanam Di Desa Cengkeh Turi Binjai - Irfan Fahreza; Agus Suriadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Elderly is someone aged ≥ 60 years, who has decreased ability to adapt to their environment and is powerless to meet their daily needs alone. The elderly often experience various kinds of problems caused by various factors such as very serious economic, social, health, psychological and physical factors. The inability of the elderly to do things related to work causes the elderly to experience a decrease in income, even though many of the elderly are still productive and can play an active role in society. Responsive steps for the welfare of the elderly are inseparable from various factors, both from the elderly themselves, the family environment, society and the government. In Law no. 13 of 1998 explained that the elderly have the right to improve their welfare, namely to get social protection and social assistance. Providing social assistance and social protection can increase dignity, self-confidence and reduce the burden on elderly families. Welfare of the elderly can be done in orphanages or non-orphanages. To increase activity and social interaction among the elderly in practicum activities, I use the stages used in social intervention at the mezzo level, which are group work stages consisting of the assessment stage, the program planning stage, the intervention stage, the evaluation stage, and the termination stage.